The Holocaust in Greece - Antōniu, Giōrgos HerausgeberIn; Moses, A. Dirk 1967- HerausgeberIn (Cambridge University Press, 2018)
"The Holocaust in Greece involved multiple actors. The German invasion in spring 1941 established three occupations regimes: Germans in the strategic areas of central Macedonia, Athens, and Thessaloniki; Italians all over Greece apart from Crete; and Bulgarians in eastern Macedonia and Thrace. For the sizeable Jewish community, these occupations posed a mortal threat. Despite the lack of credible statistics, a generally acknowledged number on the prewar Greek Jewish population is between 72,000-77,000, the Jews from Dodecanese included, albeit as Italian citizens. Some 50,000 of them resided in Thessaloniki"--